Finite Element Analysis of the Construction Strength of Semi-Submarine Glass-Bottom Catamaran - Puteri, Berliana Ayarent; Putrananda, Musdika Bagas Satria; Hutagalung, Christian Imanuel; Bahatmaka, Aldias; Aryadi, Widya (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Indonesia's extraordinary marine tourism potential requires innovation in how to enjoy it. This study discusses the innovative design of a semi-submarine glass-bottom ship for the development of marine tourism in Indonesia, which allows tourists to enjoy the beauty of the underwater world safely and comfortably. This catamaran is designed with two hulls that provide high stability and optimal deck area for tourism needs. The study focuses on analyzing the ship's frame structure using the finite element analysis method, especially on using sandwich panels that combine wood and carbon fiber materials to achieve the optimal combination of structural strength, weight, and cost efficiency. Finite element analysis shows that sandwich panels with 100% carbon fiber composition provide the best mechanical performance with a maximum stress of 615.41 MPa. The analysis shows that adding carbon fiber plays a significant role in reinforcement and is a more effective stress distributor than homogeneous materials. Although the 100% carbon fiber formulation provides the highest safety factor, the study recommends a combination of 70% wood and 30% carbon fiber, or 60% wood and 40% carbon fiber for the construction of the ship's hull frame as a more optimal solution in terms of technical and economic aspects. This ship design innovation is expected to become a new tourist attraction that introduces the beauty of Indonesia's underwater world to domestic and foreign tourists while encouraging the development of a sustainable marine tourism industry.